MODEL PREDIKSI TINGKAT KESEHATAN BANK MELALUI RASIO CAMELS - heru laksito; Nanang Nanang (Jurnal Akuntansi Indonesia, 2012)
Early from monetary crisis is which knock over Indonesia of around year 1997 - 2008 causing private sector and also “persero” banking finding difficulties finance, even happened the liquidation bank and freezed. Pursuant to the background, hence problems which wish lifted in this research is whether CAMELS ratio consisted by the CAR, KAP, APB, NPM, ROA, ROE, BOPO, LDR, and IRR have the influence in prediction mount the health of banking in period 2004-2008?.Population in this research is which banking go public with amount of sampel equal to 80 sampel of financial statement banking from 16 bank during period 2004-2008. The statistic methods which is used to test on the research hypothesis is logit regression. The result show that the financial ratio to influence the determination health of bank are ROA and IRR with the storey level significant of equal to 0,003 and 0,018. The mentioned in line with research conducted by Titik Aryani & Hekinus Manao (2002).